How do you derive the quadratic formula?

The quadratic formula is the formula that solves any quadratic equation. So, keeping things general, let's begin with a completely general quadratic equation:

ax2+bx+c=0

This is completely general because any quadratic equation can be rearranged into this form. If you find that you can't get your equation into this form, it probably isn't quadratic!

Ultimately, we want to rearrange to make x the subject. 

First, we divide through by a:

x+ (b/a)x + (c/a) = 0


Now, we 'complete the square':

(x + b/2a)^2 - b^2/4a^2 + c/a = 0

Rearranging and putting the two terms outside the bracket above a common denominator: 

(x+b/2a)^2 = (b^2 - 4ac)/4a^2

Taking the square root of both sides:

x + b/2a = +-sqrt(b^2 - 4ac)/2a

(where +- indicates we can take either the positive or negative solution)

Finally, rearranging for x:

x = (-b +- sqrt(b^2 - 4ac))/2a

Voila! Apologies for all the brackets! 

x= (-b

Answered by Aneesh N. Maths tutor

4676 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

y = Sin(2x)Cos(x). Find dy/dx.


Solve the equation x=4-|2x+1|


Find the derivative of sin(x)/x^3 with respect to x


Solve the equation 2(cos x)^ 2=2-sin x for 0 <=x<=180


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences